Interventions for the reduction of prescribed opioid use in chronic non-cancer pain - Eccleston, Christopher; Fisher, Emma; Thomas, Kyla H.; Hearn, Leslie; Derry, Sheena; Stannard, Cathy; Knaggs, Roger; Moore, R. Andrew (Wiley, 2017)
Background